The Relationship Between Febrile Convulsion and Acid-base Disturbances in Children - Jamali, Mozhdeh; Dorreh, Fatemeh; Yousefichaijan, Parsa; Khodkar, Mohammad Amin; Malik, Amirirfan (Journal of Pediatric Nephrology, 2025)
Background and Aim: Febrile seizures (FS) represent the most prevalent type of convulsive events in children. This study sought to explore the association between febrile convulsions and acid-base disturbances in children. Methods: This case-control study included 150 children aged 6 to 60 months with simple FS and 150 febrile children without seizures. Blood gas analysis was performed to measure pH, PCO2, and base excess (BE) among the children admitted to Amir Kabir Hospital in Arak, Iran. Statistical analyses, including t-test, chi-square test, and Mann-Whitney test, were conducted using SPSS software, version 18. Results: The two groups did not differ significantly in mean fever (case: 38.46±0.51 vs control: 38.45±0.59; P=0.48), pH (case: 7.49±0.06 vs control: 7.48±0.06; P=0.77), and BE (case: -2.58±3.03 vs control: -2.41±3.42; P=0.48). Although the mean arterial PCO2 in the case group was 25.1±3.51 mm Hg, which was lower than the control group’s 26±5.53 mm Hg, there was no statistically significant difference between the two groups. Conclusion: The mean venous and arterial pH values did not differ significantly in febrile children with and without seizures. Although PCO2 in pediatric patients with FS was lower than in the control group, this difference was not significant. However, due to the lack of evidence, we recommend further studies in the future.